Genotype and clinical outcomes in children with congenital adrenal hyperplasia. Issue 6 (11th April 2021) - Yoon, Ju Young; Cheon, Chong Kun
Abstract: Background: The study aimed to delineate the genotypic features and endocrine / metabolic profiles in patients with 21‐hydroxylase deficiency. Methods: Subjects were diagnosed with 21‐hydroxylase deficiency by direct Sanger sequencing or multiple ligation‐dependent probe amplification analysis and followed up in Pusan National University Children's Hospital from July 2008 to April 2019. The genotype, phenotype, and endocrine and metabolic profiles in children and young adults with congenital adrenal hyperplasia were investigated. Results: Of a total of 33 patients, 16 (48.5%) were males. Median age was 7.4 years (range, 0.1–23.8 years). Thirty (90.9%) had salt‐wasting phenotypes. Eleven (33.3%) initially presented with abnormality in a neonatal screening test without other symptoms. Among the 17 girls, seven received genital surgery. Sixty‐five alleles from the 33 patients were evaluated. The distribution of CYP21A2 gene mutations revealed an intron 2 splice site (c.293‐13A>G or c.293‐13C>G) mutation as the most common one (22, 33.8%), followed by c.518T>A (10, 15.4%) and a large deletion / conversion (7, 10.8%), in order. One novel mutation was detected, c.332del(p.G111fs). Among the 27 patients aged >2 years, fifteen (55.6%) were obese / overweight, and ten (37.0%) needed growth hormone therapy due to short stature. Among the seven subjects aged >2 years and having high‐risk genotype, five had impaired fasting glucose, three had precocious puberty, and four used growth hormone. A greater proportion of the high current corticosteroid dose group had impaired fasting glucose than in the low‐dose group (64.3 vs 23.1%, P = 0.031). Conclusions: Early monitoring of endocrine and metabolic complications from childhood might benefit patients with congenital adrenal hyperplasia.